Transformasi Peran Ibu Rumah Tangga dalam Meningkatkan Taraf Hidup Keluarga (Studi Kasus Ibu Rumah Tangga Petani Kecamatan Gurah, Kabupaten Kediri): The Transformation of the Role of Housewives in Improving the Family's Standard of Living (Case Study of Farming Housewives in Gurah District, Kediri Regency) - Laily, Dona Wahyuning; Rozci, Fatchur; Pratama, Widya Ninda (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study aims to examine the contribution of housewives to improving the economy of farming families in Bangkok Village, Gurah District, Kediri Regency. Housewives, in addition to carrying out domestic roles, also play a role in supporting the family economy through various productive activities, both in the agricultural and non-agricultural sectors. The method used in this study is a qualitative quantitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation of several informants selected purposively. The results of the study indicate that housewives make a significant contribution to increasing family income, including by helping on agricultural land, running household businesses such as trading, sewing, or producing processed foods, and managing family finances wisely. Supporting factors include family support, access to skills training, and availability of free time, while the obstacles faced include limited capital, time, and market access. Thus, housewives have an important role in encouraging the economic welfare of farming families in the village.